The formation and reactivity of α,β-unsaturated platinum carbenes: new approaches to heterocycle synthesis - Allegretti, Paul Andrew, author; Ferreira, Eric, advisor; Rovis, Tomislav, committee member; Kennan, Alan, committee member; Elliott, C. Michael, committee member; Crick, Dean, committee member (Colorado State University. Libraries, 2014)
The use of transition metal carbenes in organic synthesis has enabled chemists to promote an incredible variety of bond-forming reactions. These intermediates are traditionally accessed via the decomposition of diazo species. Alternative methods for accessing metal carbene intermediates from functional groups beyond diazo species could present many practical advantages and would complement the existing methods. Presented herein are our efforts to develop a novel method of carbene generation from the reactions of alkynes and π-acidic transition metals, and their use in the synthesis of different heterocycles. Our initial investigations focused on the ability to generate substituted furan products from the intramolecular addition of alcohols into alkynes containing propargylic methyl ethers. We then extended this reaction manifold to the synthesis of complementary positional isomers of isoxazoles, adding both propargylic N-hydroxycarbamates and propargylic N-Boc amino ethers into the activated alkyne. Key to this transformation was the inclusion of Brønsted acids to facilitate activation and elimination of the methyl ether leaving group. While studying the synthesis of furans and isoxazoles it was observed that the nature of the carbene could be modulated, leading to selective silicon or hydrogen migration. Also observed was the addition of nucleophiles into the β-position of the carbene species. This last mode of reactivity led to the discovery of a new way to synthesize vicinal bisheterocycles using alkyne activation conditions.
Keywords: heterocycles; alkyne activation; carbene